Correlative imaging using super‐resolution fluorescence microscopy and soft X‐ray tomography at cryogenic temperatures provides a new way to assess virosome solutions for vaccine development. (3rd September 2021) - Okolo, Chidinma A.; Jadhav, Archana; Phillips, Patrick; Dumoux, Maud; McMurray, Amanda A.; Joshi, Vishwas D.; Pizzey, Claire; Harkiolaki, Maria
Abstract: Active virosomes (AVs) are derivatives of viruses, broadly similar to 'parent' pathogens, with an outer envelope that contains a bespoke genome coding for four to five viral proteins capable of eliciting an antigenic response. AVs are essentially novel vaccine formulations that present on their surface selected viral proteins as antigens. Once administered, they elicit an initial 'anti‐viral' immune response. AVs are also internalised by host cells where their cargo viral genes are used to express viral antigen(s) intracellularly. These can then be transported to the host cell surface resulting in a second wave of antigen exposure and a more potent immuno‐stimulation. A new 3D correlative microscopy approach is used here to provide a robust analytical method for characterisation of Zika‐ and Chikungunya‐derivatised AV populations including vesicle size distribution and variations in antigen loading. Manufactured batches were compared to assess the extent and nature of batch‐to‐batch variations. We also show preliminary results that verify antigen expression on the surface of host cells. We present here a reliable and efficient high‐resolution 3D imaging regime that allows the evaluation of the microstructure and biochemistry of novel vaccine formulations such as AVs. Lay Description: A novel combination of microscopies involving X‐ray and laser light has been developed at the correlative cryo‐imaging beamline B24 of the UK synchrotron which can be used to analyse across‐ and within‐batch variability of active virosome vaccine formulations. We use 3D fluorescence imaging to localise viral components within vaccine vesicles and soft X‐ray tomography to characterise sample variability and impact upon delivery to cells. Moreover, we offer the next step in automation of data processing and evaluation to further enable rapid assessment of exosome‐based vaccines. Active virosome vaccines are suspensions of membrane‐bounded vesicles that carry antigens and genetic material from select viral pathogens. These elicit both an initial immune response through their introduction and a subsequent sustained antigenic potential via gene expression in host cells. In this case, as in all novel vaccine formulations, rapid assessment and batch standardisation are of paramount importance for the medical community and the methods described here provide a robust way of quick and efficient assessment and validation of formulations during research and development and at the production stages.